Endoscopic submucosal dissection for early gastric cancer in very elderly patients age 85 or older - Watanabe, Ko; Hikichi, Takuto; Nakamura, Jun; Takagi, Tadayuki; Suzuki, Rei; Sugimoto, Mitsuru, MD; Waragai, Yuichi; Kikuchi, Hitomi; Konno, Naoki; Asama, Hiroyuki; Takasumi, Mika; Obara, Katsutoshi; Ohira, Hiromasa (Endoscopy International Open, 2017)
Background and study aims The safety and efficacy of endoscopic submucosal dissection (ESD) for early gastric cancer (EGC) in very elderly patients remains unclear. The aim of this study was to evaluate the safety and efficacy of ESD for EGC in patients age 85 years and older.Patients and methods Patients who underwent ESD for EGC between September 2003 and April 2015 were divided into 3 groups: the very elderly (≥ 85 years; 43 patients), the elderly (65 – 84 years; 511 patients), and the non-elderly ( ≤ 64 years; 161 patients). Adverse events (AEs) were used as the primary endpoint to assess the safety of ESD, and the ESD treatment outcomes (i. e., en bloc resection rate, complete en bloc resection rate, and curative resection rate) and the overall survival rate after ESD were the secondary endpoints. These parameters were retrospectively evaluated in the 3 groups.Results There were no significant differences in AEs (non-elderly, elderly, and very elderly: 7.3, 9.5, and 12.5 %, respectively, P = 0.491) or in the en bloc resection and complete en bloc resection rates among the three groups. However, there was a significant difference in the curative resection rates (non-elderly, elderly, and very elderly: 91.5, 84.1, and 77.1 %, respectively, P = 0.014). Regarding overall survival, there was a significant difference among the three groups (1-, 5-, and 10-year overall survival rates: non-elderly: 98.6, 90.2, and 74.7 %; elderly: 97.2, 86.2, and 61.9 %; and very elderly: 92.7, 66.8, and 34.4 %, respectively, P = 0.001). Moreover, the overall survival rate in the very elderly patients with cardiovascular disease was significantly lower than that in the very elderly patients without cardiovascular disease (P < 0.001).Conclusions ESD is an acceptable treatment for EGC in patients 85 years of age or older in terms of safety. However, the overall survival after ESD in the very elderly patients with cardiovascular disease was short.